PENGARUH EKSTRAK KULIT BATANG ANGSANA (Pterocarpus indicus Willd.) TERHADAP KONSUMSI PAKAN KEPIK PENGHISAP BUAH KAKAO (Helopeltis theivora Wat.) - Maulidiyah, Rahmah; Sumarmin, Ramadhan; Wati, Meliya (Pendidikan Biologi, 2013)
ABSTRACT Cocoa pood sucker (Helopeltis theivora Wat.) pests attack the cocoa primordial fruit and shoot. These pests cause damage by piercing and sucking fluids fruit and young shoot. The attack led to the death of the fruit or cause the formation of abnormal fruit, consequently the yield and quality of cocoa beans decreased and the small size. This research aim to determine the effect of bark extract Angsana against exploiters cocoa pood sucker  feed consumption. This research used Completely Randomized Design ( CRD ) with 4 treatments and 6 replications . Given the control treatment (0 %), 2.5 %, 5 %, and 7.5 %. Data were analyzed using analysis of variance test then further by LSD test. This research was conducted at the Laboratory of Zoology Department of Biology Faculty of Mathematics and Natural Science UNP, at July-August 2013. The result showed concentration of 2.5 % activity of searching H. theivora takes the fastest time ( 32 minutes 65 seconds ) than other treatments. Grounding for the activity found in controls fastest time 8 minutes 89 seconds, while the 7.5 % treatment gathering activity is the fastest time 12 minutes 48 seconds. On feed intake, angsana bark extract in the treatment with a concentration of 7.5 % shows the average number of the lowest feed intake of 0.67 grams . It can be concluded that the angsana bark extract at a concentration of 5 % can be used as an antifeedant against H. theivora.